Control of Escherichia coli superoxide dismutase (sodA and sodB) genes by the ferric uptake regulation (fur) locus. - Niederhoffer, E C (1990)
The ferric uptake regulation (fur) gene product participates in regulating expression of the manganese- and iron-containing superoxide dismutase genes of Escherichia coli. Examination of beta-galactosidase activity coded from a chromosomal phi(sodA'-'lacZ) fusion suggests that metallated Fur protein acts as a transcriptional repressor of sodA (manganese superoxide dismutase [MnSOD]). Gel retardation assays demonstrate high-affinity binding of pure, Mn2(+)-Fur protein to DNA fragments containing the sodA promoter. These data and the presence of an iron box sequence in its promoter strongly suggest that sodA is part of the iron uptake regulon. An sodB'-'lacZ fusion gene borne on either a low- or high-copy plasmid yielded approximately two- to threefold more beta-galactosidase activity in Fur+ compared with Fur- cells; the levels of activity depended only weakly on the growth phase and did not change during an extended stationary phase. Measurement of FeSOD activity in logarithmic growth phase and in overnight cultures of sodA and fur sodA backgrounds revealed that almost no FeSOD activity was expressed in Fur- strains, whereas wild-type levels were expressed in Fur+ cells. Fur+ and Fur- cells bearing the multicopy plasmid pHS1-4 (sodB+) expressed approximately sevenfold less FeSOD activity in the fur background, and staining of nondenaturing electrophoretic gels indicates that synthesis of FeSOD protein was greatly reduced in Fur- cells. Gel retardation assays show that Mn2(+)-Fur had a significantly higher affinity for the promoter fragment of sodB compared with that of random DNA sequences but significantly lower than for the promoter fragment of sodA. These observations suggest that the apparent positive regulation of sodB does not result exclusively from a direct interaction of holo (metallated) Fur itself with the sodB promoter. Nevertheless, the sodB gene also appears to be part of the iron uptake regulon but not in the classical manner of Fe-dependent repression.